PENGEMBANGAN MEDIA PEMBELAJARAN JARUMIA (JAM RUMUS KIMIA) PADA SUB MATERI TATA NAMA SENYAWA BINER DI SMA NEGERI 1 TEKARANG - Eca Seponsah; Raudhatul Fadhilah; Dedeh Kurniasih (Jurnal Ilmiah Ar-Razi, 2020)
The low knowledge of student learning outcomes in the binary compound nomenclature for class X MIA at SMA Negeri 1 Tekarang is due to the difficulty and confusion of students in writing the names for binary compound nomenclature. One of the factors for the success of the learning method is the use of appropriate learning media. A learning medium is needed, namely the Jarumia learning media to make it easier for students to understand the concept of chemical compound nomenclature. This study aims to develop the Jarumia learning media in the binary compound nomenclature for class XI at SMA Negeri 1 Tekarang which is valid and practical. The instruments used were validation sheets and teacher and student response questionnaires. This type of research is the ADDIE (Analysis, design, development, implementation, evaluation) model of Research and Development (R&D). The results of the analysis show that the Jarumia learning media developed is valid with an average value of 0.93 with high criteria. The percentage of the results of the questionnaire responses to the initial field trials and the main field trials were 89.74% and 85.45%, respectively, with very practical criteria. Thus, the needle learning media developed is suitable for use as a learning medium on compound nomenclature material, especially in the binary compound sub-material.